Strategic Choice and Operational Performance: A comparative study of commercial banks in Oman - Y. Sree Rama Murthy, James Rajasekar, (Opción, 1970)
The objective of this paper is to investigate various strategiesadopted by banks in the Sultanate of Oman and to explore how thesestrategies may have helped these banks overcome different operationaldifficulties during periods of crisis. The empirical analysis in this studywas done using binary logit regression technique with data from theBank Scope database. Data was drawn from the balance sheets andincome statements of commercial banks, and this data ranges fromDecember 1999 to December 2017. Data from 1999 to 2009 was usedfor estimating the logit equations, and data from 2012 to 2017 wasused for testing the predictive ability of the model. From a strategypoint of view, our study of Omani banks focuses on the financial crisesof 2000-2001 and 2008-2009, and the model predictions for years2012 to 2017 brings forth the following conclusion: In order to ensurethat a bank performs well (in terms of profit and asset growth), thebank’s management should focus on capital account management,interest spread management, good loan quality, and high loan-todepositratios. Finally, we also found that cost management andliquidity management are two areas of strategic choices that are notparticularly important.